Intergenerational economic mobility in Mexico - Campos Vázquez, Raymundo M.; Delgado Barrera, Victor H.; Vélez-Grajales, Roberto (Estudios Económicos de El Colegio de México, 2020)
This article documents several measures of intergenerational economic mobility in Mexico. We employ census data available for 1990 to 2015 on earnings. Since censuses do not link individuals over time, the empirical strategy follows a synthetic approach by matching individuals with synthetic family earnings by the state where they were born and their birth cohort. The aggregate estimate indicates an intergenerational elasticity (IGE) of 0.50, adjusted for cross-country comparison; intergenerational mobility is low in comparison with advanced economies. Results also suggest a higher intergenerational mobility for younger cohorts. Moreover, people born in southern Mexico have a lesser degree of intergenerational mobility.